Implantación de la contabilidad comercial en la empresa Mundo Digital de la ciudad de Loja en el período enero - marzo del 2013 - Espinoza Reyes, María Alejandra (2014)
The introduction of accounting COMMERCIAL ENTERPRISE DIGITAL WORLD. Was developed in order to make known to the owner of record economic movements in a clear, orderly, methodical and according to the laws, principles and accounting standards for the calculation of the economic, financial, for pipetting investment decisions and thus improve customer service and as a student to get the engineering degree in Accounting and Auditing. Fulfilling the objectives are determined to request supporting documentation allowing orderly record the memorandum of operations and proceed with the physical count of the assets, rights and obligations held by the company at the beginning of the accounting period, then devised the plan and accounts manual will be used in the company, following the accounting process was developed the Balance Initial Daybook which economic movements recorded chronologically according to the principles of double entry and international accounting standards these accounts were mayorizadas in the General Staff, to check their balances was necessary to prepare the Trial Balance, Worksheet, the respective settings for reliable financial statements, comparable and relevant. Finally it is concluded that records were developed that allowed controlling merchandise such as transcript, purchase and sales assistants also took monthly VAT declarations and entire accounting process for the permanent system has ordered and systematic way so its owner is recommended continuing the implementation of commercial accounting comfortable for preparation of financial statements for making decisions.